An assessment of the natural marking patterns used for photo-identification of common minke whales and white-beaked dolphins in Icelandic waters. (22nd May 2015) - Bertulli, Chiara G.; Rasmussen, Marianne H.; Rosso, Massimiliano
Abstract : Natural marks occurring in cetaceans are used to measure population parameters, social structure and movements. However, the changeable nature of these marks can originate bias in these estimates. The aim of this work was to calculate abundance and prevalence of 28 mark types observed in common minke whales and white-beaked dolphins photographed in Icelandic waters for 11 years (2002–2013) in order to identify reliable markings which could be suitable for capture-mark-recapture studies. In the common minke whale subsample the most prevalent occurring marks were cookie-cutter shark bite, notch and lamprey bite, and herpes-like lesions and blisters were the most abundant. White-beaked dolphins had notch, fin patches and fine scrape as the most prevalent, and black mark and fine scrape were the most abundant. Loss and gain rates were also estimated resulting in eight mark types with no losses in common minke whales including fin outline and injury marks. In white-beaked dolphins there were 13 mark types with null loss rate among which there were notch, distinct notch and amputation. Our findings confirm that fin and injury marks are among the most accurate features to use for capture-mark-recapture studies as noted for other cetacean species. We also suggest including cookie-cutter shark bites for common minke whales and fin patches for white-beaked dolphins due to their low loss rate. These two mark types were amongst the most prevalent in both species, so their addition will be pivotal in increasing the power of analysis conducted using photo-identification data obtaining more accurate population estimates.